DEVELOPMENT OF PHYSICS ASSESSMENT USING MARBLES GAME CONTEXT TO MEASURE CRITICAL THINKING SKILLS - Heldalia, Heldalia; Wiyatmo , Yusman (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2026)
Critical thinking is a core competency in 21st-century education. However, students’ critical thinking skills in physics learning remain relatively low, particularly in problem analysis and argument construction. Previous studies have developed various assessment instruments to measure critical thinking skills, but these instruments are generally not contextualized within local cultural practices and are rarely designed specifically for momentum and impulse topics. Furthermore, the integration of traditional games as a context for authentic assessment has not been widely explored. This study employed a Research and Development (R&D) design based on the ADDIE model, involving 324 eleventh-grade students from several schools in Yogyakarta for empirical validation. This instrument consists of eight essay items designed based on critical thinking indicators and validated by six validators. Content validity was analyzed using Aiken’s V, while empirical validity, reliability, and item difficulty were examined using the Rasch model with the Partial Credit Model (PCM). The results show that all items achieved high content validity (Aiken’s V = 0.833–1.00) and met the Rasch model fit criteria, as indicated by acceptable INFIT and OUTFIT MNSQ values and positive point measure correlations (PTMEA CORR). The instrument also demonstrated high reliability (Item Reliability = 0.87; Person Reliability = 0.85), with a moderate level of item difficulty. The instrument demonstrates strong validity and reliability, as well as high measurement precision in differentiating students’ levels of critical thinking skills.